Бром в торфах Томской области - Бернатонис В. К. Вилис Казимирович; Архипов В. С. Виктор Сергеевич; Резчиков В. И. Владимир Иванович; Балабаев Д. Ю. Дмитрий Юрьевич (1989, 1989)
В фонде НТБ ТПУ отсутствует